2023
DOI: 10.3390/rs15082075
|View full text |Cite
|
Sign up to set email alerts
|

Driving Mechanism of Differentiation in Urban Thermal Environment during Rapid Urbanization

Abstract: To achieve sustainable urban development, it is essential to gain insight into the spatial and temporal differentiation characteristics and the driving mechanisms of the urban thermal environment (UTE). As urbanization continues to accelerate, human activity and landscape configuration and composition interact to complicate the UTE. However, the differences in UTE-driven mechanisms at different stages of urbanization remain unclear. In this study, the UTE of Shenyang was measured quantitatively by using the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…Second, artificial construction activities in Shaanxi Province are closely related to the spatio-temporal variation in AAT (Figure 4), which may increase the intensity of UTE [18,41], resulting in the deterioration of the UTE in different areas between 1970 and 2017, including the Southern, Central, and Northern regions. This is consistent with previous studies conducted in Shaanxi Province [28,33] which found that significant changes in the UTE have been observed in the northwest and southeast of Shaanxi Province. Due to having imperious surfaces which absorb solar radiation and releasing long-wave radiation [28], which directly warms the air, vegetation reduces solar radiation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, artificial construction activities in Shaanxi Province are closely related to the spatio-temporal variation in AAT (Figure 4), which may increase the intensity of UTE [18,41], resulting in the deterioration of the UTE in different areas between 1970 and 2017, including the Southern, Central, and Northern regions. This is consistent with previous studies conducted in Shaanxi Province [28,33] which found that significant changes in the UTE have been observed in the northwest and southeast of Shaanxi Province. Due to having imperious surfaces which absorb solar radiation and releasing long-wave radiation [28], which directly warms the air, vegetation reduces solar radiation.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies conducted in Shaanxi Province [28,33] which found that significant changes in the UTE have been observed in the northwest and southeast of Shaanxi Province. Due to having imperious surfaces which absorb solar radiation and releasing long-wave radiation [28], which directly warms the air, vegetation reduces solar radiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The socioeconomic factor typically refers to human activities and industrial production and can be quantified by population density (PD) and industrial added value (IAV) [25][26][27]. The increase in PD and IAV tends to be accompanied by elevated heat emissions, thereby resulting in a rise in LST [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of research methodology, the previous methods employed include statistical analysis, ordinary least squares regression (OLSR), and machine learning methods, such as neural network models and random forests [25,37,38]. However, statistical analysis and OLSR are inadequate in capturing the nonlinear relationship between LST and IFs.…”
Section: Introductionmentioning
confidence: 99%